2006
DOI: 10.1038/nmat1563
|View full text |Cite
|
Sign up to set email alerts
|

Optical trapping and integration of semiconductor nanowire assemblies in water

Abstract: S emiconductor nanowires have received much attentionowing to their potential use as building blocks of miniaturized electrical 1 , nanofluidic 2 and optical devices 3 . Although chemical nanowire synthesis procedures have matured and now yield nanowires with specific compositions 4 and growth directions 5 , the use of these materials in scientific, biomedical and microelectronic applications is greatly restricted owing to a lack of methods to assemble nanowires into complex heterostructures with high spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
314
1
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 395 publications
(326 citation statements)
references
References 30 publications
(31 reference statements)
0
314
1
3
Order By: Relevance
“…screen charge | atomic force microscopy | piezoresponse | charge scraping F erroelectric and piezoelectric materials have attracted great attention due to their applications in commercial markets such as a medical imaging (1-3), next generation inkjet printer heads (4), precision-positioning stages (5,6), fuel injectors in diesel engines (7,8), and memory devices (9,10). The macroscopic properties of ferroelectric and piezoelectric materials that make them appealing for current and future technologies can be more fully understood and improved through detailed knowledge of their domain structures at the nanoscale and mesoscale (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…screen charge | atomic force microscopy | piezoresponse | charge scraping F erroelectric and piezoelectric materials have attracted great attention due to their applications in commercial markets such as a medical imaging (1-3), next generation inkjet printer heads (4), precision-positioning stages (5,6), fuel injectors in diesel engines (7,8), and memory devices (9,10). The macroscopic properties of ferroelectric and piezoelectric materials that make them appealing for current and future technologies can be more fully understood and improved through detailed knowledge of their domain structures at the nanoscale and mesoscale (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…In addition, the latest experiments 10 demonstrated that these nanostructures can be used as local mechano-optical probes. 11,12 Although many groups report on the synthesis and structural characterization of different types of alkaline niobate nanowires, there are no comparative studies that address their nonlinear optical response. In this work, we compare SHG signal and waveguiding properties for three types of perovskite alkaline niobate nanowires such as NaNbO 3 , KNbO 3 , and LiNbO 3 (XNbO 3 ).…”
mentioning
confidence: 99%
“…One fraction of the wires is usually already stuck to the glass coverslip, while the rest of the nanowires and nanowire clusters undergo Brownian motion allowing us to easily test both geometries using the same setup and same sample cell (details regarding the setup can be found in Supporting Information). When the laser is brought close to a nanowire, it is pulled into the trap, 11 trapped tridimensionally perpendicular to the surface and the SHG signal can be detected by the EMCCD camera. Varying the polarization of the impinging light, by moving a half wave plate the reliance of the SHG signal on light polarization is studied.…”
mentioning
confidence: 99%
“…single molecule ͉ subnanometer resolution ͉ signal-to-noise ratio S ince the discovery that optical gradients could stably trap micrometer-sized dielectric particles (1), gradient optical traps, or optical tweezers, have been used in a large variety of applications ranging from microfabrication (2,3) to the study of colloidal hydrodynamics (4-6) and nonequilibrium thermodynamics (7)(8)(9)(10). In particular, the use of calibrated optical springs has provided unprecedented new insight on the mechanical properties of single biological molecules and the molecular motors that manipulate them in the cell (11)(12)(13)(14).…”
mentioning
confidence: 99%